A new combined heating and power system driven by biomass for total-site utility applications. (January 2021) - Amiri, Hamed; Sotoodeh, Amir Farhang; Amidpour, Majid
Abstract: Steam generation of the industrial steam networks through an internal process driven by a renewable energy can be extremely demanding. Conventionally, fossil fuels are used for this aim since a high-temperature heat source is needed to reliability drive a steam network. To address this demand and decrease environmental penalty associate with the conventional methods, an innovative and high-efficient biomass-driven cogeneration system is proposed for the real need of the utility systems by considering a suitable total-site heat recovery and distribution mechanism. The proposed cogeneration system consists of a biomass gasifier, a gas turbine cycle, a solid oxide fuel cell, and a steam network unit. In comparison with the previous cogeneration systems, the steam required for the gasification process in the gasifier is supplied by some portion of the steam generated at the last stage of the steam network unit. Also, natural gas is used as an auxiliary fuel to satisfy the surplus fuel required for the steam generation. A new methodology is introduced to use a biomass-driven cogeneration system as a primary steam generator of the steam network unit instead of using a conventional boiler or gas turbine with heat recovery steam generator. The proposed system produces additional heating load of 235.26 MW in comparison with the topping system (i.e., combined solid oxide fuel cell/gas turbine system). Integrating the steam network unit also increased the energy efficiency of the basic system from 20.05% to 54.35% and the net power from 47.55 MW to 72.3 MW. The proposed integrated system can be regarded as a promising futuristic layout for simultaneous steam and power generation of the petrochemical industries. Graphical abstract: Image 1 Highlights: An innovative biomass-based cogeneration heat and power is devised for process industrial. The proposed system is designed to work in total site context. Integrating steam network system with the combined system boosted net power from 47.55 MW to 72.3 MW. Thermal efficiency of the basic system is increased from 20.05% to 54.35% with the current model. Net electricity/heating ratio was obtained 0.307, indicating that the devised system was dominant in terms of power.